2018
DOI: 10.1007/s13139-018-0521-1
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Tracers for Nuclear Cardiac PET Imaging

Abstract: Myocardial perfusion imaging using positron emission tomography (PET) has several advantages over single photon emission computed tomography (SPECT). The recent advances in SPECT technology have shown promise, but there is still a large need for PET in the clinical management of coronary artery disease (CAD). Especially, absolute quantification of myocardial blood flow (MBF) using PET is extremely important. In spite of considerable advances in the diagnosis of CAD, novel PET radiopharmaceuticals remain necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…The results indicated that 5MEF specifically targeted mitochondria in cardiomyocytes and achieved much stronger fluorescence intensity than normal cells. These data suggest that 5MEF may be a promising probe for assessment of myocardial mitochondrial dysfunction. ,, …”
Section: Results and Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…The results indicated that 5MEF specifically targeted mitochondria in cardiomyocytes and achieved much stronger fluorescence intensity than normal cells. These data suggest that 5MEF may be a promising probe for assessment of myocardial mitochondrial dysfunction. ,, …”
Section: Results and Discussionmentioning
confidence: 75%
“…These data suggest that 5MEF may be a promising probe for assessment of myocardial mitochondrial dysfunction. 16,17,35 Animal Fluorescence Imaging. Ex vivo fluorescence imaging of 14 F16s was performed for tissues harvested from BALB/c mice at 2 h post injection of the probes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations